X-ray CT observations of selective damage of mineralised synthetic particles by high voltage pulses. (November 2019) - Huang, Wei; Ren, Fei; Shi, Fengnian; Steel, Karen
Highlights: A mineralised particle and a barren particle in pair subjected to one high voltage pulse loading. X-ray CT used to extract cracks/micro-cracks generated in the synthetic particles. The majority of cracks/micro-cracks found in the particles embedded with metalliferous grains. The breakdown channels traveled through the metalliferous grain rather than its boundary. Abstract: High voltage pulse (HVP) selective weakening and selective breakage of mineralised particles have been previously reported. It was hypothesised that these effects were a consequence of metalliferous grains-induced electrical breakdown, but no microscale evidence was presented to test the hypothesis. In the present study, synthetic particles made of grout were cast with a single grain of metalliferous mineral embedded, or with many grains of fine metalliferous mineral dispersed, or with no metalliferous mineral present at all (the barren particle). HVP tests were performed in which a pair of synthetic particles consisting of a mineralised particle and a barren particle were subjected to one pulse loading. The HVP products were examined by X-ray Computed Tomography (X-ray CT) to extract the cracks/micro-cracks and domain breakdown channel propagation behavior. X-ray CT images showed that the majority of the cracks/micro-cracks were generated in the metalliferous grain(s) embedded synthetic particles, whereas no cracks/micro-cracks were observed in the barren particles. The X-ray CT images also confirmed that the electrical breakdown channels traveled through the metalliferous grains rather than through the grain boundary between the grout and the metalliferous grain, which had a detrimental effect upon the integrity of the metalliferous grains. The effect of metalliferous grain-induced HVP selective damage of mineralised particles is used to elucidate the mechanisms of HVP selective weakening and selective breakage of mineralised particles.